RESIDENTS’ ATTITUDE TO SOLID WASTE MANAGEMENT IN SELECTED QUARTERS IN OWO, ONDO STATE, NIGERIA - Lawrecno Akin, Famakinwa; Agunloye, Odogiyon (International Journal of Research -GRANTHAALAYAH, 2018)
This work appraised residents attitude to domestic solid waste management in selected quarters in Owo, Ondo State, Nigeria. It identified types of domestic solid waste generated and examined the residents’ perception of waste management at the three selected quarters in Owo which include Rufus Giwa Polytechnic Area, GRA and Iloro Quarters. Data were obtained directly from the targeted population using structured questionnaire and personal observations. The questions provided in the questionnaire were directed to the household population in the area. Meanwhile, photography was used for on-the-spot assessment of the conditions of some domestic solid waste spots in the study area. For the purpose of this research, systematic random sampling technique was adopted in the administration of questionnaire on residents of the three selected quarters in Owo, Ondo State. The univariate techniques of data analysis in form of tables, and photographs which describes the necessary features of the data set. Larger percentage of the respondents emptied their receptacles when it is filled. The research recommended that the federal government of Nigeria should partner with International Development Agencies to improve domestic solid waste management in the area.